The Effect of A White Noise on Sleep Quality Among Critically Ill Patients in Indonesia: A Randomized Controlled Trial - Nurhayati, Nunung; Waluyo, Agung; Kariasa, I Made; Jahja, Umar (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction:Sleep disturbance is a frequent problem among critically ill patients and may adversely affect recovery. White noise has been proposed as a non-pharmacological approach to reduce environmental disruption and improve sleep; however, evidence from Indonesian intensive care units (ICUs) is currently lacking. Objectives:This study aimed to evaluate the effect of white noise exposure on sleep quality among critically ill patients treated in ICUs in Indonesia. Methods: A randomized controlled trial was performed in the ICUs of three public hospitals in West Java, Indonesia, involving adult ICU patients. The intervention group received white noise twice daily for three days, while controls received standard care. Sleep quality was measured using the RCSQ and analyzed with repeated-measures ANOVA, Cohen’s d, and GEE models. Results: Final analyses included 25 participants in the intervention group and 25 in the control group. Sleep quality in the intervention group showed a significant improvement at the third measurement point, with a moderate effect size (d = 0.42). No significant changes were observed in the control group. GEE analysis demonstrated a significantly greater improvement in sleep quality in the intervention group compared with the control group after three days (β = 6.43, p 0.001). Conclusions:White noise intervention was associated with improved sleep quality among critically ill ICU patients. These findings support the incorporation of acoustic management strategies into ICU care to enhance patient comfort and recovery.